BACTERIOLOGICAL TEST OF WATER FROM DUG WELL THAT DOES NOT FULFILL REQUIREMENT IN THE WORKING AREA PUTRI AYU HEALTH CENTERS, SUB TELANAI PURA OF JAMBI, 2015 - Lipinwati - -; Aromatika L; Armaidi Darmawan (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2016)
Abstract Background:  The incidence diarrhea in Jambi is still quite high, especially in infants with 10936 cases. The highest incidence was in Putri Ayu health centers.  One of the associated factors with diarrhea is water supply does not fulfill requirement.  In the working area of Putri Ayu health centers, most people use dug well as one of the sources of water supply,  but there are some dug wells have unfulfill requirement physical conditions. Dug well water is vulnerable to contamination by bacteria. The purpose of this study was to know the MPN index of coliform bacteria, the microscopic images of coliform bacteria and the quality of dug well water. Methode :  This study was a descriptive with laboratory experimental design. The samples were 25  unfulfill requirement dug well water that conducted using proportionate stratified random sampling method from April to July 2015. Result :  From 25 samples, there are 21 water samples (84%) has a number of coliform that over the maximum levels are allowed by SK. Dirjen PPM and PLP No. 1/PO.03.04.PA.91 and SK JUKLAK PKA 2000/2001, that is 50 MPN/100 ml. From microscopic images, there are 19 samples (76%) had gram-negative bacteria with red and short rod-shaped and six other samples (24%) is a gram-positive bacteria with purple and cocci shaped. Conclusion: There are coliform bacteria contamination in dug well water in the working area of Putri Ayu health centers.  This result might be influenced by physical condition of dug well. Keywords:  Dug well water, coliform, MPN